Ագուլիսի ԺԸ. դարի հայ վաճառական Խոջա Հովհաննեսի փաստաթղթերը Մատենադարանի կաթողիկոսական դիվանում - Կոստիկյան, Քրիստինե (Մատենադարան)
Together with the archive of St. Tovma monastery, the documents of some Armenian merchants of Agulis have survived in the archive of the Catholicosate of Matenadaran. A considerable number (about 100) of these documents belonged to Khoja Hovhannes, the son of Srapion, a wealthy merchant of Agulis in the first half of 18th century. On the basis of these documents, the article discusses the life and activities of this merchant, with a parallel research on the history of Agulis in that period. The study has allowed to trace some of his trade activities in Agulis, the Ottoman Empire and his cooperation with the merchants involved in the transit trade through Eastern Transcaucasia. Some details of his estates in Agulis, Vanand, Terunis etc. and his other possessions in Ordubad are revealed, as well as his administrative and social activities. By the example of the edicts granted to Khoja Hovhannes, the article refers to the problems and difficulties which the merchants faced in Iran under the rule of Nadir Shah and the following years till 1754. В Матенадаране, в архиве армянских католикосов, а также в архиве монастыря Св. Фомы в Агулисе сохранились документы некоторых агулисских купцов. Значительную часть (около 100 единиц) этих материалов составляют документы, принадлежащие предприимчивому купцу 18-го века Ходжe Ованесу, сыну Срапиона из Агулиса. В статье на основании этих документов исследуется жизнь и деятельность этого купца параллельно с событиями истории Агулиса того периода. Документы позволяют проследить некоторые из его торговых сделок в Агулисе, Османской империи и сотрудничесто с купцами, вовлеченными в транзитную торговлю через Восточное Закавказье. Выявлены также некоторые детали, касающиеся его имений в Агулисе, Вананде, Терунисе, имущества в Ордубаде, а также его социально-административной деятельности. На примере грамот, полученных Ходжой Ованесом, рассмотрены также проблемы и трудности, с которыми сталкивались купцы Ирана в период правления Надир шаха и последующие годы, вплоть до 1754 г.
Keywords: Արխիվային նյութեր; Միջազգային առցանց գիտաժողով